Factors affecting Academic Performance in Middle School Children in Government and Private Schools of Bahawalpur (Medical Forum Monthly, 2024)
Objective: The objective of this study was to assess the factors affecting academic performance of middle school children in public and private sector schools of Bahawalpur City.Study Design: Descriptive / Cross sectional Study Place and Duration of Study: This study was conducted at the Government Abbasia Higher Secondary Model School and Moon System of Education (private school) Bahawalpur from February 2016 to June 2016.Materials and Methods: This study was conducted in Middle school (7th and 8th class). The data was collected through a pre-formed questionnaire. Data was analyzed by using SPSS version 15. Percentages and frequencies were calculated. Figures were made.Results: In this study 200 students were included, out of which Government Abbasia Higher Secondary Model School Bahawalpur, the students with poor academic performance were 28%, fair academic performance were 23%, good academic performance were 49% and in Moon System of Education Bahawalpur (Private School), the students with poor academic performance were 2%, fair academic performance were 23%, good academic performance were 75%In Abbasia School academic performance of students whose fathers were Illiterate was Poor 73.4%, Fair 13.3%, Good 13.3%. Academic performance of students whose fathers had education Up to Metric was Poor 24.2%, Fair 28.8%, Good 47% and academic performance of students whose fathers had education Above Metric was Poor 5.3%, Fair 10.5%, Good 84.2%.Conclusion: Our study concluded that that parents' education, socioeconomic status and parents' assistance in homework are directly related with academic performance of students.